The impact of volunteering with a student-run free clinic on medical student specialty selection - Kyle B. Thomson; Pranav Mirpuri; Melissa Chen (BMC Medical Education, 2022)
Abstract Background The shortage of primary care physicians in the United States is expected to grow to 17,800–48,000 physicians by 2034. Student Run Free Clinics are an increasingly popular component of medical schools and may provide an avenue for increasing medical student interest in primary care specialties. However, there is limited research on the impact of Student Run Free Clinics on medical student specialty choice. This investigation sought to determine whether volunteering with the Interprofessional Community Clinic (ICC), the Student Run Free Clinic associated with Chicago Medical School, was associated with an increased likelihood of matching into primary care specialties. Secondarily, the authors investigated associations between volunteering and matching into family practice. Finally, the authors explored associations between volunteering and the competitiveness of specialty choice. Methods This retrospective review utilized data on medical school graduates from 2015 – 2021 including their matched specialties, the number of ICC shifts they volunteered for, and whether they held an ICC leadership position (executive officers). Primary care specialties were defined as internal medicine, family practice, pediatrics, or combined internal medicine/pediatrics. Residency fill rate was used as a proxy for competitiveness. Results This analysis included 506 medical students (254 ICC volunteers and 252 non-volunteers). Among ICC volunteers, 47.2% matched into a primary care specialty compared to 36.5% of non-volunteers (RR 1.29, 95% CI 1.05–1.59). Each additional shift worked at the ICC was correlated with increased odds of matching into family practice by a factor of 1.042 (95% CI 1.005–1.079). Conclusions Medical students who volunteered with the ICC were more likely to match into primary care residencies. Students who volunteered more frequently were more likely to match into family practice. Further investigation is warranted to determine whether these associations are causative and could thus be leveraged to encourage medical students to pursue primary care careers.